Violence and Newborn Health : Estimates for Colombia - Rodriguez, Laura (World Bank, Washington, DC, 2020)
This paper examines the relationship between maternal exposure to violence during pregnancy and newborn birthweight. The paper exploits variation in the timing of exposure and in the geographic location of expectant mothers across Colombian municipalities. Exposure to violence in early pregnancy had a large negative impact on birthweight, primarily for boys, and the effect was mitigated by their mothers' education. Girls were affected mainly by shocks in later stages of gestation. Furthermore, their mothers were more likely to engage in potentially harmful behaviors during the pregnancy. This evidence exposes the importance of parental responses in shaping the effect of exposure to violence on newborn health.